Penentuan Muka Air dan Jenis Lapisan Tanah Menggunakan Metode Geolistrik - Randhi Saily; Harnedi Maizir; Ridho Azhari (Universitas Islam 45, 2023)
The tools that are often used, such as sondir and SPT, are quite heavy and require a long measurement time span, making it difficult to determine the shear strength of the soil, both in the laboratory and in the field.. This study uses the resistivity geoelectric method of the Wenner Alpha configuration supported by the Naniura NRD 300 HF tool. The aim is to determine the estimated groundwater level and determine the resistivity value of each type of soil layer below the surface of the study area. This study performs 2D measurements to calculate 1-D and 2-D geoelectric resistivity with electrodes arranged lengthwise to form a straight line. Using the IP2WIN software, the measurement results are processed to produce a 2D apparent resistivity section that describes the color image distribution values of the soil surface layer. The measurement results on track 1 shows a resistivity value between 3,512 – 1.539 Ω.m with a length of 90 m at a depth to 15.05 m. The predicted groundwater level elevation is located 0.656 meters below the surface of the ground. Track 2 has a span length of 60 meters and resistivity values ranging from 29.55 to 207.1.m, with a predicted groundwater level at a depth of 0.72 m below the surface. The types of soil layers are clay mixed with sand, sand mixed with gravel and sandstone mixed with gravel.